TEACH MY CHILDREN ENGLISH: WHY PARENTS WANT ENGLISH TEACHING FOR THEIR CHILDREN - Patrisius Istiarto Djiwandono (Indonesian JELT, 2005)
This paper describes parents’ reasons for sending their children to an English language course, their expectations from the English language instruction, and the disadvantages they perceive in getting their children to learn English at their early ages. A small-scale exploratory survey using questionnaires was conducted among 46 parents whose children learn English at a private course. The results indicate that the majority of the parents are generally aware of the practical values of providing English instruction for their children and hardly perceive any disadvantages in this early English learning. Also, they expect English instruction to enable their children to perform the four language skills, notably speaking. Implications for the young learners’ first language as well as the teaching of young learners are then presented. These may offer teachers, parents, and other researchers some important points to consider.Keywords: parents, young learners, English language teaching.